Hubungan Konsep Diri dan Perilaku Bullying di Kalangan Remaja SMP Negeri 3 Gamping, Sleman, Yogyakarta - Azizah, Fajriyati Nur; Azizah, Iqlima Nurul (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2025)
Background: Adolescence is prone to mental health problems and aggressive behavior. Adolescent self-concept is very important because it can affect bullying behavior. Adolescent self-concept, both positive and negative, affects bullying behavior. Purpose: This study aims at determining the relationship between self-concept and bullying on SMPN 3 students in Gamping, Sleman, Yogyakarta. Method: This study used a non-experimental quantitative design with a crosssectional approach. The data were collected at SMP Negeri 3 Gamping, Sleman, Yogyakarta with a population of 346 students in grades VI, VII, and VIII. The sample consisted of 60 respondents who were selected using a stratified random sampling approach. The data collection was conducted by using questionnaires, and the statistical analysis used Mann-Whitney test. Result: The adolescent self-concept of SMP N 3 students in Gamping, Sleman, Yogyakarta demonstrates negative self-concept of 66 (68.8%). Meanwhile, the majority of adolescents at SMPN 3 Gamping, Sleman, Yogyakarta tend to have a moderate level of bullying behavior, with a percentage of 90.6%. Conclusion: In the statistical analysis, there is a significant relationship between self-concept and bullying behavior in adolescents at SMP Negeri 3 Gamping, Sleman, Yogyakarta with a p- value of 0.000 and. Its Z score is -4.506, indicating that the relationship between the two variables is negative.